Gender-Based Violence Is a Human Rights Violation: Are Donors Responding Adequately? What a Decade of Donor Interventions in Colombia, Kenya, and Uganda Reveals - Clarisa Bencomo; Emily Battistini; Terry Mcgovern (Harvard FXB Center for Health and Human Rights, 2020)
Gender-based violence (GBV) is a violation of human rights and must be addressed as such. This paper examines whether donor practices align with a rights-based approach, using data from our comprehensive study of foreign funding flows related to GBV in Colombia, Kenya, and Uganda from 2010 to 2020. By analyzing data from 1,180 grants-and providing parallel analyses of the state of GBV, and GBV reporting and interventions in each country-we demonstrate donors' role in shaping GBV outcomes and their consequent duty to address policies and practices that violate rights. Accordingly, we propose changes in donor practices to promote realization of the right to freedom from violence.